Report of the Scottish Departmental Committee on the North Sea Fishing Industry : report , part 1 - Conacher, H.M.; Moffat, J. (London : Scottish Departmental Committee on the North Sea Fishing Industry, 1914)
Bibliotheek E. Anseele
Engels
Verslag
Keywords: visserij; Noordzee